Desain Masterplan Direktorat Sistem Teknologi Informasi Universitas Teknologi Sumbawa Menggunakan Framework Garuda Smart City - I Made Widiarta; Shinta Esabella; Nora Dery Sofya; Erwin Mardinata (STMIK Budi Darma, 2022)
The purpose of this study was to design a master plan for the Directorate of Information Systems and Technology, Sumbawa University of Technology (UTS), an educational institution located in Sumbawa, West Nusa Tenggara Province with an area of 60 hectares, has 32 study programs and has 3,772 active students. Master plan create using the smart campus model adopted from the Garuda Smart City framework. The smart campus model consists of three main models, namely smart people, smart governance, and smart infrastructure, technology and environment. The development of intelligent people includes services to Education Personnel (Tendik), services to teaching staff, and services to students. Meanwhile, smart governance refers to a written document issued officially in the form of a circular letter by the Directorate of Systems and Information Technology. The third model, namely smart infrastructure, technology and environment which includes hardware and software. With the draft master plan for the Directorate of Information Systems and Technology, this is one way to realize good quality, efficient and integrated information technology services for the entire academic community of the Sumbawa University of Technology